Foreign Trade Intelligence Centers in Türkiye: The Impact of Global Trade Dynamics and Advances in Big Data - Yördem, Aslıhan (Fırat University, 2025)
Export-oriented growth strategies have been pivotal in shaping critical economic indicators such as national income, growth rates, industrialization, and employment, thereby assuming a determinative role in the global economy. In response to the growing complexity of international trade and the intensification of global competition, governments have introduced a range of both explicit and implicit support mechanisms. These measures are to guide firms toward global markets while concurrently enhancing their ability to strengthen their competitive advantage. This shift has precipitated a substantial increase in the demand for precise, timely, and actionable data, which has become indispensable for entering international markets, evaluating risks, forecasting trends, and adapting to the dynamic nature of global trade. In this landscape, advanced data technologies have emerged as transformative drivers of change in international trade. This study provides a comprehensive analysis of the foreign trade intelligence centers recently established in Türkiye, with particular emphasis on their operational structures and competitive intelligence frameworks in the context of global trade dynamics and big data advancements. In addition, the research identifies key areas where improvements are necessary to enhance the effectiveness of the centers, offering critical insights into how Türkiye can optimize its trade intelligence capabilities

İhracat odaklı büyüme stratejileri, milli gelir, büyüme oranları, sanayileşme ve istihdam gibi önemli ekonomik göstergelerin şekillenmesinde büyük rol oynamakta ve bu sayede küresel ekonomide belirleyici bir konum kazanmaktadır. Diğer taraftan uluslararası ticaretin giderek daha karmaşık hale gelmesi ve küresel rekabetin artmasıyla birlikte, hükümetler açık ve örtük çeşitli destek mekanizmaları geliştirmiştir. Bu önlemler, firmaları küresel pazarlara yönlendirirken aynı zamanda rekabet avantajlarını güçlendirmeyi ve kapasitelerini artırmayı hedeflemektedir. Bu süreç, uluslararası pazarlara girmek, riskleri değerlendirmek, eğilimleri tahmin etmek ve küresel ticaretin dinamik yapısına uyum sağlamak için doğru, zamanında ve eyleme dönüştürülebilir veriye olan talebin artmasına neden olmuştur. Bu ortamda, ileri veri teknolojileri uluslararası ticaret uygulamalarında önemli bir dönüşüm yaratma potansiyeline sahip itici güçler olarak ön plana çıkmıştır. Bu çalışma, bilhassa küresel ticaret dinamikleri ve büyük verideki gelişmeler bağlamında operasyonel yapıları ile rekabet istihbarat çerçevelerine vurgu yaparak, Türkiye’de son yıllarda kurulan dış ticaret istihbarat merkezlerinin kapsamlı bir analizini sunmaktadır. Ayrıca, araştırma, bu merkezlerin etkinliğini artırmaya yönelik iyileştirilmesi gereken alanları belirleyerek, Türkiye'nin ticaret istihbaratı kapasitesini daha etkili hale getirme konusunda önemli içgörüler sağlamaktadır
Türkiye’de Dış Ticaret İstihbarat Merkezleri: Küresel Ticaret Dinamikleri ve Büyük Veri Alanındaki Gelişmelerin Etkisi
Keywords: Big Data; Büyük Veri; Foreign Trade; Dış Ticaret